2000
DOI: 10.1006/jfan.2000.3602
|View full text |Cite
|
Sign up to set email alerts
|

Global Compactness Properties of Semilinear Elliptic Equations with Critical Exponential Growth

Abstract: Sequences of positive solutions to semilinear elliptic equations of critical exponential growth in the plane either are precompact in the Sobolev H 1 -topology or concentrate at isolated points of the domain. For energies allowing at most single-point blow-up, we establish a universal blow-up pattern near the concentration point and uniquely characterize the blow-up energy in terms of a geometric limiting problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
159
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(172 citation statements)
references
References 18 publications
9
159
0
4
Order By: Relevance
“…We also prove a structural theorem for bounded sequences in W 1,N 0 (B), where B = B 1 (0) is a unit ball in R N , which is similar to Struwe's "global compactness" [12] and its subsequent refinements known in the case N > p. (Note that global compactness results in [3,11] while providing asymptotic behavior of bounded sequences in W 1,N 0 , use the different blowup transformations than this paper and end up with asymptotic profiles supported in the whole R N .) Our starting point for this result is the following version of global compactness, see [14,Theorem 5.1]:…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We also prove a structural theorem for bounded sequences in W 1,N 0 (B), where B = B 1 (0) is a unit ball in R N , which is similar to Struwe's "global compactness" [12] and its subsequent refinements known in the case N > p. (Note that global compactness results in [3,11] while providing asymptotic behavior of bounded sequences in W 1,N 0 , use the different blowup transformations than this paper and end up with asymptotic profiles supported in the whole R N .) Our starting point for this result is the following version of global compactness, see [14,Theorem 5.1]:…”
Section: Introductionmentioning
confidence: 70%
“…[1][2][3]7])) as it deals with general bounded sequences rather than with critical sequences of specific functionals. Provided that a suitable extension of transformations (1.6) to non-radial functions is found, an analysis based such transformations appears to be more promising than the study of blow-ups based on the ination on the linear scale.…”
mentioning
confidence: 99%
“…To do this, following the analogous argument in [14], for any x ∈ R N , we can find ρ ∈ [1,2] such that the solution φ m of the Dirichlet problems…”
Section: Thus We Havewmentioning
confidence: 99%
“…In [16] S.Yan generalizes this global compactness result to the case of p-Laplacian successfully. Very recently, Adimurthi and M.Struwe in [1] have studied the convergence of (P.S.) sequences of the energy functional associated with a semilinear elliptic problem on a bounded domain in R 2 with critical nonlinearity f (s) growing like exp(4πs 2 ) as s → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…The case of a single semilinear elliptic equation in bounded subsets of R 2 has been investigated by several authors, see for example [2,3,5,6]. It has been observed that criticality in dimension two is connected with the imbedding of…”
Section: Introductionmentioning
confidence: 99%